Modelos pedagógicos aplicados en el proceso de enseñanza aprendizaje dentro de la Unidad Educativa Emilio Terán. - Escobar Ronquillo, Alex David (2022)
The objective of this study is to determine the pedagogical models through the analysis in the teaching-learning process for academic strengthening in the Fifth grade parallel "A" EEBB within the Emilio Terán Educational Unit year 2021-2022, considering the great importance of research for the proper management of these elements, It is for this reason that it is necessary to understand about the pedagogical models as orientators in the teaching-learning process within the educational institutions, in addition, it should be emphasized that, despite the fact that teaching is guided by them, educators come with difficulties to employ them correctly due to different circumstances. In order to carry out this research, it was supported by the methodology that goes according to the developed process, starting from the interpretative paradigm with a qualitative approach, which makes it possible to understand the context, the research is of descriptive and explanatory type, the applied method was the inductive one, finally, it should be noted that it was applied to a population of 35 students and 1 teacher as their interveners. As the main conclusion of the research developed, it is evident that the pedagogical model used by the teacher within the teaching-learning process in the Educational Unit subject of study was constructivist, the present study contributed with a vision about what happens inside the classroom, objectives, contents, resources, and methodologies that develop in the construction of the new knowledge without inconveniences. Finally, the theoretical analysis carried out for the research led the researchers to identify the socio-critical pedagogical model as an alternative to improve the teaching and learning processes.